Microsatellite instability in colorectal cancer - de' Angelis, Gian Luigi; Bottarelli, Lorena; Azzoni, Cinzia; de' Angelis, Nicola; Leandro, Gioacchino; Di Mario, Francesco; Gaiani, Federica; Negri, Francesca (Acta Biomedica Atenei Parmensis, 2018)
Microsatellites are short tandem repeat DNA sequences of one to tetra base pairs distributed throughout the human genome, both in coding and non-coding regions. Owing to their repeated structure, microsatellites are particularly prone to replication errors that are normally repaired by the Mismatch Repair (MMR) system. MMR is a very highly conserved cellular process, involving many proteins, resulting in the identification, and subsequent repair of mismatched bases, likely to have arisen during DNA replication, genetic recombination or chemical or physical damage. Proteins within the MMR system include MLH1, PMS2, MSH2, MSH6, MLH3, MSH3, PMS1, and Exo1. Deficient MMR (dMMR) results in a strong mutator phenotype known as microsatellite instability (MSI), characterized by widespread length polymorphisms of microsatellite sequences due to DNA polymerase slippage. MSI is recognized as one of the major carcinogenetic pathways of colorectal cancer (CRC): it represents a molecular hallmark of hereditary nonpolyposis colorectal cancer (HNPCC), also known as Lynch syndrome (LS); moreover it is detected in 15% of sporadic colorectal cancers, more often due to an epigenetic inactivation of MLH1. Identification of MSI CRC is important, as MSI may serve as a screening tool for detecting LS, a prognostic marker for patient outcome, and a predictive marker for response to chemotherapy and to immunotherapy.